The impact of big data analytics on organizational sustainability: The influencing factors of autonomous research and development and absorptive capacity. (18th November 2022) - Arshad, Muhammad; Kun Yu, Chen; Qadir, Aneela; Ahmad, Waqar; Rafique, Muhammad
This study aims to see how the big data analytics capability (BDAC) and its dimensions affect the absorptive capacity and autonomous R&D of high-speed railways. As well as their impact on the organization's long-term sustainability, using the mediation of absorptive capacity and autonomy in R&D. Employees and the heads of the planning, HR, R&D, and technical departments of high-speed railways were polled for information. For data analysis, we used PLS-SEM, and then we employed mediation analysis. BDAC increases the organization's ability to tolerate change and gives management instructions on making decisions. This study adds to the body of knowledge on absorptive capacity development and autonomy over R&D activities by investigating the role of BDAC in the long-term development of high-speed trains.